The study of employee satisfaction and burnout syndrome in healthcare workers - Vezhnovets’, Tetyana (ScienceRise: Medical Science, 2017)
Aim. Determination of burnout syndrome formation features in healthcare workers “satisfied” and “not satisfied” with their job for the further development of recommendations to prevent it. Methods. The study of employee satisfaction in 164 healthcare workers of Kherson city clinical hospital named after E. E. Karabelesh (Kherson, Ukraine) by questionnaire (response was 87 %). The responders answered the question: "Are you satisfied with your job at the hospital?". The answers were evaluated by 7-point scale. The responders were divided in two groups according their answers: the first group (n=120) consisted of the satisfied with job (7, 6, 5 points), the second group (n=34) consisted of the not satisfied with job (3, 2, 1 points). The responders (n=10) answered “can not decide” (4 points) were removed from the further analysis. Results. It was found that the share of people having burnout syndrome among the “not satisfied” (65.0 %) is significantly higher (р<0,05) comparing to the “satisfied” group (40.0 %). In the responders from the “not satisfied” group, the symptoms of “stressful circumstances experiencing" (46 %), “professional duties reduction” (38 %), “depersonalization” (35 %), “expansion the scope of keeping emotions” (30 %), “inadequate selective emotional response” (27 %) manifested the most often. In the “satisfied” group, the symptoms of “expansion the scope of keeping emotions” (15 %) and “stressful circumstances experiencing" (14 %) were the most frequent manifestation of burnout syndrome. There is a negative relationship between employee satisfaction and the level of severity of burnout syndrome (Р<0,001). Conclusion. The probability of burnout syndrome is higher in healthcare workers unsatisfied with their job. In these workers the syndrome leads to deterioration professional capacity and decrease in quality of medical care by “professional duties reduction” and “depersonalization” symptoms. In the “satisfied” workers it leads to quality of communication and their health deterioration by “expansion the scope of keeping emotions” and “psychosomatic and psycho-vegetative violations” symptoms. Employee satisfaction is a factor for burnout syndrome prevention